Simulated tsunami evacuation behavior of local residents and visitors in Kamakura, Japan. (August 2017) - Takabatake, Tomoyuki; Shibayama, Tomoya; Esteban, Miguel; Ishii, Hidenori; Hamano, Go
Abstract: Currently, it is believed that evacuation is the most effective method of protecting lives from tsunamis, in particular after the events of the 2011 Tohoku Earthquake Tsunami. In many coastal areas tsunamis pose a threat not only to local residents, who know the area well, but also to visiting tourists, and thus it is important to consider both these groups when preparing evacuation plans. However, while numerous studies and simulations on tsunami evacuation have been made, research focusing on the influence of visitors on evacuation processes is limited. To clarify this the authors developed an agent-based tsunami evacuation model which considers the different behavior of local residents and visitors, which can estimate the evacuation time, number of individuals reaching each evacuation area, the location of bottlenecks and the number of casualties. The model was applied to study the case of Yuigahama Beach, Kamakura, Japan, with results indicating that the behavior and number of visitors have a significant impact on evacuation processes, especially the location of bottlenecks and the number of casualties. Results also show that heavy congestion will occur during evacuation in places where there are many visitors and thus, in such a situation, the decrease of the moving speed owing to the congestion needs to be appropriately taken into account to simulate the evacuation process. It can be concluded that reducing congestion (i.e., widening roads, guiding visitors to less congested roads) is a crucial countermeasure for a sight-seeing location to reduce the casualties that can result from a tsunami.